2004
DOI: 10.1128/aem.70.6.3500-3505.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Escherichia coli O157:H7 to pH Alters Membrane Lipid Composition, Verotoxin Secretion, and Resistance to Simulated Gastric Fluid Acid

Abstract: The influence of adaptation to pH (from pH 5.0 to 9.0) on membrane lipid composition, verotoxin concentration, and resistance to acidic conditions in simulated gastric fluid (SGF) (pH 1.5, 37°C) was determined for Escherichia coli O157:H7 (HEC, ATCC 43895), an rpoS-deficient mutant of ATCC 43895 (HEC-RM, FRIK 816-3), and nonpathogenic E. coli (NPEC, ATCC 25922). Regardless of the strain, D values (in SGF) of acid-adapted cells were higher than those of non-acid-adapted cells, with HEC adapted at pH 5.0 having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(76 citation statements)
references
References 38 publications
6
70
0
Order By: Relevance
“…Others have reported either no change or reduced Stx production after acid adaptation alone (Duffy et al, 2000;Leenanon et al, 2003;Yuk & Marshall, 2004). To our knowledge this is the first study to report no effect of either acute acid stress or acid-adapted acid stress on Stx production.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Others have reported either no change or reduced Stx production after acid adaptation alone (Duffy et al, 2000;Leenanon et al, 2003;Yuk & Marshall, 2004). To our knowledge this is the first study to report no effect of either acute acid stress or acid-adapted acid stress on Stx production.…”
Section: Discussionmentioning
confidence: 58%
“…In another study, a gadE (encoding an acidresistance regulator) mutation resulted in increased adhesion of E. coli O157 : H7 to colonic epithelial cells, again suggesting negative regulation of one or more adhesins during acid stress (Tatsuno et al, 2003). Other studies have reported that production of Shiga toxin is sensitive to culture conditions including pH (Duffy et al, 2000;Yuk & Marshall, 2004). However, to our knowledge there have been no studies of EHEC virulence changes after more severe acid stress, typical of that encountered during gastric passage, nor studies linking an acid-stressed EHEC virulence phenotype with transcriptional changes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, as mentioned above, resistance of acetic acid-habituated cells to pH 3.5 increased in the order 15°C Ͼ 10°C Ͼ 4°C, despite the fact that their resistance to acetic acid during acid habituation in the washings was the opposite (Table 1). This reversal in acid resistance of E. coli O157:H7 may be associated with the ability of cells to maintain synthesis of acid shock proteins and increases in the proportions of saturated fatty acids in their membranes (1,25,45) to cope with sequent acid stresses when habituated at temperatures above, but not below, their minimum growth limit. Additional studies including evaluation of potential alterations at the cellular level are required to elucidate these acid stress responses of E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that even relatively small changes in the genome (single-nucleotide polymorphisms [SNPs] as well as insertions and deletions [indels]) can have substantial effects on the phenotype and fitness of the strains (13,169). Mutations can take place in structural genes influencing membrane fluidity (246); in metabolic enzymes they can reroute carbon and energy fluxes and increase metabolic efficiency (65,101); and in regulatory elements or in the transcription machinery (e.g., transcription factors and the RNA polymerase or promoter region) they can have effects on transcription/translation speed, transcript stability, and strength of induction and repression of genes (40). It has been demonstrated that organisms adapt rapidly on the molecular level to changing environmental conditions by increasing mRNA expression levels (11,41,47,93).…”
Section: Implications Of Genome Heterogeneity and Plasticitymentioning
confidence: 99%